Keseimbangan kehidupan dunia dan akhirat dalam perspektif al-qur’an dan hadis - Fudhla, Mahmudatun; Alfath Anam, Hazbi Maulana; Mauludya, Dita (Maliki Interdisciplinary Journal, 2025)
The balance between worldly life and the afterlife in Islamic teachings is a fundamental principle for Muslims in living their lives. Islam teaches that worldly life is not the final goal, but rather a means to collect good deeds as provisions for the eternal afterlife. Through a study of the verses of the Qur’an, such as in QS Al-A’la, Al-Qashash, and Ali Imran, as well as the hadith of the Prophet Muhammad SAW, it is explained that a Muslim is required to not only focus on worldly success such as wealth, career, and education, but also pay attention to worship, morals, and good social relationships. This study uses a literature study method by reviewing various Islamic literature to describe how the Qur’an and hadith provide guidance in balancing these two aspects of life. The results of the discussion show that the balance between the world and the afterlife will result in a harmonious life, full of blessings, and prevent someone from extreme attitudes in living only one side of life. With a complete understanding of this principle, it is hoped that Muslims can live a more meaningful life and be blessed by Allah SWT.